2021
DOI: 10.3389/fcell.2021.743652
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Characterization Analysis Identifies an Oncogenic Pseudogene RP11-3543B.1 in Human Gastric Cancer

Abstract: Background: Gastrointestinal Cancer (GICs) is the most common group of malignancies, and many of its types are the leading causes of cancer related death worldwide. Pseudogenes have been revealed to have critical regulatory roles in human cancers. The objective of this study is to comprehensive characterize the pseudogenes expression profiling and identify key pseudogenes in the development of gastric cancer (GC).Methods: The pseudogenes expression profiling was analyzed in six types of GICs cancer from The Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Besides, many pseudogenes can also crosstalk with protein-coding genes by acting as ceRNAs to sequester shared miRNAs. For example, RP11-3543B.1 has been identified as an oncogenic pseudogene that implicated in GC pathogenesis by regulating MAPK4 expression via a ceRNA mechanism ( 14 ). However, there is little evidence for pseudogene-related prognostic signatures in GICs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, many pseudogenes can also crosstalk with protein-coding genes by acting as ceRNAs to sequester shared miRNAs. For example, RP11-3543B.1 has been identified as an oncogenic pseudogene that implicated in GC pathogenesis by regulating MAPK4 expression via a ceRNA mechanism ( 14 ). However, there is little evidence for pseudogene-related prognostic signatures in GICs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, pseudogenes were initially believed to be nonfunctional RNAs [9]. Recently, increasing evidence has shown that pseudogenes could regulate the progression of various tumors [10][11][12]. e Misato family member 2 (MSTO2P) pseudogene was found to be implicated in gastric cancer [13], lung cancer [14] and HCC [15].…”
Section: Introductionmentioning
confidence: 99%